Assessment of behavioral characteristics of patients with depressive disorder variables in psychiatric unit in sulaimani general hospital - Jassim, Arazo A. (Sulaimani Journal for Pure and Applied Sciences, 2013)
The objective of the study is to assessing the behavioral characteristics of patients with depressive Disorder. A descriptive study was conducted with the aim of the study. To obtain reliable and valid data, a questionnaire was developed according to the objectives of the study. A questionnaire consists of 2 parts, each of which aimed at collecting information and data as follows, part(I): general information concerning patient's socio-demographical characteristics, part (II): A list of 40 items describing expected behavioral characteristics in seven aspects. A purposive sample is used which consists of (50) in-patients in psychiatric unit in sulaimani general hospital. The patients and their relatives were interviewed for data collection procedure. The empirical field work was carried out. Descriptive and inferential statistical methods were used in the analysis of the results using mean and SD to describe behavioral characteristics. The findings revealed that the most depressive patients with the age around 35.5 years, mostly female (68%), married (58%), un employed (68%) and have low level of education, as 42% of them have basic education and 36% illiterate. In addition, the findings revealed that high mean score of 12 behavioral characteristics are identified by aspects, in negative self-concept, three behaviors are identified: "patients feel not respected by other" (M=1.84), "where no good qualities" (M=1.54) and" have no self worth" (M=1.50). In social detachment the behavior is "I prefer to sit alone" (M=1.66). In passivity "I feel I am pushed by others to actions when I am not ready" (M=1.560). In somatic complaint, the patient behaviors that have their " appetite (M=2.92), sleep (M=2.88), weight (M=2.66) are not increased. In depressive verbal content "I believe that life is nothing" and "I wish I could get rid of my life" M=1.50 and Abnormal traits "patients believe that people are unfair in interacting with them" (M=1.60).
Keywords: behavioral characteristics; depressive disorders